That the people might live : Native American literatures and Native American community - Weaver, Jace, 1957- (Oxford University Press, 1997)
Weaver focuses on studying Native American literature as a reflectionand shaper of community values, especially for modern urban Native Americans. For cultures so gravitized by oral tradition, the written word has become the messenger of culture and religion.